(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRAC: In accordance with the results of research in the field shows that the coaching of athletes in the District Talaud islands are less sustainable. Athletes only get awards and a variety of services in the last event of the championship, after the completion of the event and there is no longer a championship, then in general the athlete is no longer considered and will be sought at the time held more championships. It is an important task for local governments in general and the Department of Education Youth and Sports in particular that would be an assurance for athletes who have the name of the area. This type of research is qualitative, focusing on the field of research in the form of case studies (case study) directly to the Department of Education Youth and Sports Talaud Islands. Informants were taken as many as 13 people, which is 5 employees Department of Education Youth and Sports, 4 athletes and 4 members of the public. The focus of research is more emphasis on the availability of infrastructure as the primary means of supporting the success in the development of athletic performance. Not optimal role of the Ministry of Youth and Sports in guidance increase athletic performance as well as the lack of attention in the provision of facilities and infrastructure development of athletes. development of national sport is still first, just as a routine oriented instant achievement based on past experience poor innovation. That is what causes athletes Talaud Islands minimal achievements both at the provincial and national level. Therefore it needs financial support in supporting the activities of athletic performance, local government more organized and held sporting-iven championship-scale regional and national, further enhanced the development of advice infrastructure supporting sport in this case is a gymnasium complete with the football stadium and other facilities necessary reward for athletes who excel through appointed Administrative State Civil or provide housing facilities that simple. Key words: The Role of Local Government, Facilities and Infrastructure Development of Athletes